Pengaruh Pendekatan Pembelajaran (Problem Based Learning dan Discovery Based Learning) dan Motor Educability Siswa Terhadap Penguasaan Keterampilan Dasar Renang Gaya Bebas Dan Gaya Dada - Septian, Regi Dwi; Hendrayana, Yudy; Ugelta, Surdiniaty; Nugraha, Reshandi; Riansyah, Riansyah; Abdullah Al Ghazaly, Muhammad Dzikry (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
] The purpose of this study is to obtain data on the effects of the Problem Based Learning and Discovery Based Learning approach, as well as the level of Motor Educability students have on freestyle swimming skills and breaststroke. The method used in this study was an experiment with a 2x2 factorial design. The population in this study were students of the Bandung City Chemica Vocational School and the Bandung City Binadharma High School, with a total sample of 64 students. The instruments used in this study were the IOWA Brace Test, and the Freestyle and Chest Style Skill Test. The results showed that: There was a significant effect of the Problem Based Learning and Discovery Based Learning approach to freestyle swimming skills and breaststroke in students who had high Motor Educability. There is a significant effect of Problem Based Learning and Discovery Based Learning approaches on freestyle swimming skills and breaststroke in students who have low Motor Educability. The conclusion in this study is Problem Based Learning and Discovery Based Learning and seeing the results of Motor Educability owned by students are proven to have a positive influence on improving student swimming skills. Keywords: Discovery Based Learning, Motor Educability Problem Based Learning